Combine-ARMS: a rapid and cost-effective protocol for molecular characterization of beta-thalassemia in Malaysia - Tan, K.L.; Tan, J.A.M.A.; Wong, Y.C.; Wee, Y.C.; Thong, M.K.; Yap, S.F. (2001)
beta -Thalassemia major patients have chronic anemia and are dependent on blood transfusions to sustain life. Molecular characterization and prenatal diagnosis of beta -thalassemia is essential in Malaysia because about 4.5 of the population are heterozygous carriers for beta -thalassemia. The high percentage of compound heterozygosity (47.62) found in beta -thalassemia major patients in the Thalassaemia Registry, University of Malaya Medical Centre (UMMC), Malaysia, also supports a need for rapid, economical, and sensitive protocols for the detection of beta -thalassemia mutations. Molecular characterization of beta -thalassemia mutations in Malaysia is currently carried out using ARMS, which detects a single beta -thalassemia mutation per PCR reaction. We developed and evaluated Combine amplification refractory mutation system (C-ARMS) techniques for efficient molecular detection of two to three beta -thalassemia mutations in a single PCR reaction. Three C-ARMS protocols were evaluated and established for molecular characterization of common beta -thalassemia mutations in the Malay and Chinese ethnic groups in Malaysia. Two C-ARMS protocols (cd 41-42/IVSII #654 and -29/cd 71-72) detected the beta -thalassemia mutations in 74.98 of the Chinese patients studied. The C-ARMS for ed 41-42/IVSII #654 detected beta -thalassemia mutations in 72 of the Chinese families. C-ARMS for ed 41-42/IVSI #5/cd 17 allowed detection of beta -thalassemia mutations in 36.53 of beta -thalassemia in the Malay patients. C-ARMS for ed 41-42/IVSI #5/cd 17 detected beta -thalassemia in 45.54 of the Chinese patients. We conclude that C-ARMS with the ability to detect two to three mutations in a single reaction provides more rapid and cost-effective protocols for beta -thalassemia prenatal diagnosis and molecular analysis programs in Malaysia.